Allometric Models for Estimating Carbon Fixation in Citrus Trees - Quinones, Ana; Martínez-Alcántara, Belén; Font, Antonio; Forner-Giner, María A.; Legaz, Francisco; Primo-Millo, Eduardo; Iglesias, Domingo J. (2017)
Citrus fruits play an important part in the Spanish agricultural sector. These orchards could play an important role as a terrestrial C sink and contribute to C fixation. We proposed quantifying the net primary production in different-aged citrus trees through the measurement of annual increases in the C content of the biomass of trees of different ages completely excavated. The measured net primary production in mature citrus was 27 kg C tree(-1) (1143 g C m(-2) yr(-1); 11.4 Mg C ha(-1) yr(-1)) with a similar behavior to that of different forests. Moreover, in this experiment, allometric equations for the estimation of annual net primary production in citrus orchards based on the relationship between net primary production and biometric variables were established. These equations could be a useful tool to calculate the potential C fixation in citrus areas. Canopy volume was the best variable for predicting above- and belowground biomass. Leaf area index and trunk diameter could also be selected as reliable and easily measurable variables to estimate net primary production in the whole tree.